2018
DOI: 10.4103/jfmpc.jfmpc_117_18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bronchial asthma and its associated risk factors in school-going adolescents in Tier-III North Indian City

Abstract: Background:Asthma is one of the most common chronic diseases of childhood and a major health problem not only in India but globally. Despite multifold increase in prevalence, there is paucity of data on bronchial asthma from non-metro cities. The objectives were to find prevalence of bronchial asthma and various risk factors that are associated in this age group and determine the extent of under diagnosis.Materials and Methods:A cross-sectional study involving 927 students from four government and three privat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…[ 4 5 ] However, the rates are higher among children 2.3–5.14% and adolescents 3.3–13.1%. [ 6 7 8 9 ] These were similar across age groups when compared with data across the globe. [ 10 11 ] Phase 3 of ISAAC study and recent studies revealed that the prevalence of asthma among children had reached a plateau phase in western countries compared to African and Asian countries where the numbers are still increasing.…”
Section: Introductionmentioning
confidence: 70%
“…[ 4 5 ] However, the rates are higher among children 2.3–5.14% and adolescents 3.3–13.1%. [ 6 7 8 9 ] These were similar across age groups when compared with data across the globe. [ 10 11 ] Phase 3 of ISAAC study and recent studies revealed that the prevalence of asthma among children had reached a plateau phase in western countries compared to African and Asian countries where the numbers are still increasing.…”
Section: Introductionmentioning
confidence: 70%
“…[ 4 ] Underreporting and misdiagnosis of asthma are important contributors to variations in the number of asthma cases reported by various workers. [ 5 ] “Indian Study on Epidemiology of Asthma, Respiratory Symptoms, and Chronic Bronchitis” (INSEARCH) reported a prevalence rate of was carried out in the adult population and to be 2.05% during 2007-09, with an estimated burden of about 17.23 million in 2011. [ 6 ] The National Family Health Survey had predicted asthma at ~2% during 2005-06.…”
Section: Asthma Epidemiologymentioning
confidence: 99%
“…[ 8 ] Exposure to smoke, dust, pollen, or any other allergen, or high humid weather trigger asthmatic reactions and the condition may be delayed by preventing the exposure. [ 5 ] Asthma is widely penetrated in rural areas. [ 9 ] The asthma cases are largely under-reported.…”
Section: Asthma Epidemiologymentioning
confidence: 99%
“…It affects 10% of the world's population and creates a serious social and economic burden. Children and adolescents are more likely to suffer from, [ 3 ] adults are also vulnerable, and it repeatedly attacks, affecting work and life, causing great distress to adults. The main drugs used in BA are glucocorticoid,β2 receptor agonist, anticholinergic agent, theophylline, leukotriene receptor antagonist, mast cell membrane stabilizer and others.…”
Section: Introductionmentioning
confidence: 99%